REKAMAN ELEKRONIK PERSONAL CHAT PADA SOCIAL MEDIA SEBAGAI ALAT BUKTI - I PUTU KRISNA ADHI (Media Iuris, 2018)
Abstract:This journal is titled "Personal Chat Electronic Record on Social Media as a Proof Tool". The problem formulation of this journal contains how a Personal Chat can be used as a legitimate evidence in front of the court seen from Indonesia's positive law and also the comparison of some personal chat features on some social media that can be used as valid evidence in court. This writing uses a normative legal research method by linking various sources related to the validity of the Personal Chat as a valid proof. The reason for using normative due to the obscurity of norms in national rules regarding the verification of Personal Chat in court. The conclusion of this journal is in accordance with the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which will then be referred to as the ITE Law, Electronic Information and / or Electronic Documents and / or results the print is a valid legal proof, and this Personal Chat is a proof of evidence that the Personal Chat as a proof cannot stand alone. The requirement for Personal Chat to become evidence in the trial is that it has fulfilled the formal and material requirements, accompanied by expert information or digital forensics, fulfills the verification of authentication and also the necessity of merging with other evidence as a provision for the minimum principle of evidence. Regarding the use of personal chat as a legitimate means of proof it is also not immediately obtained from various social media, but from several social media applications that have fulfilled the standardization of authenticity and security guarantees.Keywords: Electronic Recordings, Personal Chat, Social Media, Digital Evidence.Abstrak:Jurnal ini berjudul "Rekaman Elektronik Personal Chat Pada Social Media Sebagai Alat Bukti". Rumusan masalah jurnal ini berisikan tentang bagaimana suatu Personal Chat tersebut dapat dijadikan sebagai alat bukti yang sah dimuka pengadilan dilihat dari hukum positif Indonesia dan juga komparasi dari beberapa fitur personal chat pada beberapa social media yang dapat dijadikan alat bukti yang sah dimuka persidangan. Penulisan ini menggunakan metode penelitian hukum normatif dengan mengaitkan berbagai sumber yang berkaitan dengan keabsahan Personal Chat tersebut sebagai alat bukti yang sah. Alasan mempergunakan normatif dikarenakan kekaburan norma dalam aturan nasional mengenai pembuktian Personal Chat di dalam pengadilan. Kesimpulan dari jurnal ini yaitu sesuai dengan -Undang Republik Indonesia Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik yang selanjutnya akan disebut Undang-Undang ITE, Informasi Elektronik dan/atau Dokumen Elektronik dan/atau hasil cetaknya merupakan alat bukti hukum yang sah, serta Personal Chat ini sebagai alat bukti petunjuk dimana Personal Chat sebagai alat bukti tidak dapat berdiri sendiri. Syarat agar Personal Chat menjadi alat bukti dalam persidangan adalah telah memenuhi syarat formil dan materiil, disertai oleh keterangan ahli atau digital forensik, memenuhi kasifikasi otentifikasi dan juga keharusan penggabungan dengan alat bukti lain sebagai sebuah ketentuan adanya prinsip minimum alat bukti. Mengenai penggunaan personal chat sebagai alat bukti yang sah juga tidak serta-merta didapat dari berbagai social media akan tetapi dari beberapa aplikasi social media yang sudah memenuhi standarisasi otentisitas dan jaminan keamanan.Kata kunci : Rekaman Elektronik, Personal Chat, Social Media, Alat Bukti.